Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) Cuci Tangan Pakai Sabun (CTPS) Pada Siswa di Sekolah Dasar - Dian Paramitha Asyari; Fadhilatul Hasnah (STIKes Alifah Padang, 2023)
Clean and healthy living behavior is a set of behaviors that are practiced on the basis of awareness as a result of learning, which makes a person, family, group or community able to help themselves (independently) in the health sector and play an active role in realizing public health. One of the indicators of Clean and Healthy Lifestyle is Washing Hands with Soap (CTPS). The Covid-19 situation is also forcing all groups to continue to implement clean and healthy living behaviors by washing hands with soap, especially for school-age children. There were 13 cases of diarrhea in elementary school children. The purpose of this service is to provide direction to elementary school children about the importance of CTPS. The results of the pretest and posttest showed that 47 students did not know how to wash their hands properly and correctly.